I mean, everybody is kinda racist.: PowerPoint Presentations in Social-Studies Classrooms in Germany - Torrau, Sören (Journal of social science education, 2019)
Purpose: PowerPoint presentations have changed representations of knowledge. They represent a social transformation process of communication which is also reflected in social-studies classrooms. Thus, it is important to examine not only how students hold presentations but also to explore the construction of knowledge through presentations: What are the didactic functions? Methodology: The article focuses on a case study that was part of a doctoral dissertation that uses audio recordings, interviews and classroom observations in order to explore presentations in social-studies classrooms. Findings: A presentation – the shooting of Michael Brown – by 10 th -grade student Laura shows: Students select and transform knowledge in a socio-constructivist and didactic way. Presentations are the starting point of a process of negotiation of knowledge, which is triggered by the presenting students. Laura asks within the lesson: What is racism and what can we learn about racial structures? By reading the article teachers can learn about teaching students about race and racism through presentations. (Orig.).